Safety, tolerability and appropriate use of nintedanib in idiopathic pulmonary fibrosis. Issue 1 (December 2015) - Corte, Tamera; Bonella, Francesco; Crestani, Bruno; Demedts, Maurits; Richeldi, Luca; Coeck, Carl; Pelling, Katy; Quaresma, Manuel; Lasky, Joseph
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a progressive disease characterised by dyspnea and loss of lung function. Methods Using pooled data from the replicate, randomized, 52-week, placebo-controlled INPULSIS® trials, we characterized the safety and tolerability of nintedanib 150 mg twice daily in patients with IPF and described how adverse events were managed during these trials. Results One thousand and sixty- one patients were treated (nintedanib 638; placebo 423). Higher proportions of patients in the nintedanib group than the placebo group had ≥1 dose reduction to 100 mg bid (27.9 % versus 3.8 %) or treatment interruption (23.7 % versus 9.9 %). Adverse events led to permanent treatment discontinuation in 19.3 % and 13.0 % of patients in the nintedanib and placebo groups, respectively. Diarrhea was the most frequent adverse event, reported in 62.4 % of patients in the nintedanib group versus 18.4 % in the placebo group; however, only 4.4 % of nintedanib-treated patients discontinued trial medication prematurely due to diarrhea. Monitoring of liver enzymes before and periodically during nintedanib treatment was recommended so that liver enzyme elevations could be managed through dose reduction or treatment interruption. Conclusion Nintedanib had a manageable safety and tolerability profile in patients with IPF. Recommendations for adverse event management minimized permanent treatment discontinuations in the INPULSIS® trials. Trial registration clinicaltrials.govNCT01335464 andNCT01335477